Does the COVID-19 Pandemic Affect Women-Owned Firms Differently? - Abebe, Girum; Bundervoet, Tom; Wieser, Christina (Washington, DC: World Bank, 2020)
The COVID-19 (coronavirus) pandemic and its negative economic effects create an urgent need for timely data and evidence to help monitor and mitigate the social and economic impacts of the crisis and protect the welfare of the least well-off in Ethiopia's society. To monitor the impacts of the COVID-19 (coronavirus) pandemic on Ethiopia's economy and people and inform interventions and policy responses, the World Bank Ethiopia team, in collaboration with the government, designed and implemented two high-frequency phone surveys, one with firms and one with households.